P14.46 SUBEPENDYMAL GIANT CELLS ASTROCYTOMA (SEGA) IN TUBEROUS SCLEROSIS COMPLEX (TSC): A SERIES OF 31 PATIENTS. (6th September 2019) - Giordano, F; Moscheo, C; Lenge, M; Mari, F; Grandoni, M; Buccoliero, A; Sardi, I; Genitori, L; Guidi, M
Abstract: Background: Subependymal Giant Cells Astrocytomas (SEGAs) are characteristic of Tuberous Sclerosis Complex (TSC). They are usually benign tumors but may rapidly grow and cause hydrocephalus and raised intracranial pressure. Surgery is mandatory for large and symptomatic SEGAs METHODS: 31 patients harboring SEGAs in TSC were admitted for surgery. The main indications for surgery were tumor size and location, tumoral growth and cystization/hemorrhage, and hydrocephalus. In presence of symptomatic hydrocephalus firts surgery aimed to reduce intracranial pressure RESULTS: Forty-four surgeries were performed in 31 patients achieving Gross Total and Subtotal Removal in 36 and 8 patients respectively. Recurrences occurred in 11 patients; nine of them were reoperated while two were administered therapy with m-TOR pathway inhibitors. Surgical morbidity and mortality accounted for 22.7% and 2.3% respectively; hydrocephalus was the main complication. After an average follow-up of 5 years, 90% of patients had no evidence of the disease and most (93, 3%) had a good clinical status after surgery; 12 out of 30 patients (40%) had a VP-shunt for hydrocephalus Conclusions: GTR is feasible and represents the treatment of choice of SEGAs in TSC. Therapy with m-TOR pathway inhibitors is to be considered in selected patients and especially in recurrences of SEGAs